THE RELATIONSHIP OF FIXED ASSET REVALUATION TO PERCEPTION OF PERFORMANCE: EVALUATION OF TAX POLICY - Darmawan, Andi; Sinaga, Andar Ramona; Wibowo, Arie (Jurnal Akuntansi dan Keuangan Indonesia, 2022)
This study aimed to know the relationship between fixed asset revaluation and the perception of the company's performance in the future. This research can advise the government on the effect of fixed asset revaluation on company performance when the government repeats the policy of reducing fixed asset revaluation taxes during the economic recovery during the pandemic. The methodology used in this study was mixed methods research, which collected and analyzed qualitative and quantitative data. This research used primary data from focus group discussions (representatives of industrial entities, tax consulting practitioners, public accountants, regulators, and related authorities) and questionnaires distributed to 118 listed companies. This research found that implementing fixed asset revaluation in the company has an effect on increasing the company's performance perception in terms of accounting-based measures but did not necessarily increase the company's performance perception in terms of market-based measures. This research also explored the company's motives for revaluing fixed assets and the factors that became obstacles to implementing the fixed-asset revaluation tax incentive policy in Indonesia, including recommendations for implementing the fixed asset revaluation tax policy in the future.